Computational Screening of Functional Monomers for Esculetin Recognition Using a Semiempirical Tight-Binding Approach - Dia Indah Azhari; Akmal Djamaan; Aiyi Asnawi; Purnawan Pontana Putra (JSFK (Jurnal Sains Farmasi & Klinis), 2026)
Esculetin is a bioactive coumarin derivative with reported antioxidant, anti-inflammatory, and anticancer activities. Despite its pharmacological relevance, achieving selective molecular recognition of esculetin in complex systems remains challenging. Computational screening of functional monomers offers a rational strategy to identify candidates capable of forming stable noncovalent interactions with the target molecule. In this study, 21 monomers were evaluated using a semiempirical extended tight-binding (xTB) approach. Initial screening was performed through automated interaction site screening (aISS) to estimate interaction energies. The aISS results identified 4-vinylbenzeneboronic acid as having the most favorable interaction energy (-312.87 kcal/mol), followed by 2-Acrylamido-2-methyl-1-propanesulfonic acid (-25.34 kcal/mol), p-vinylbenzoic acid (-24.71 kcal/mol), trans-3-(3-pyridyl)acrylic acid (-23.04 kcal/mol), and 9-vinylcarbazole (-22.17 kcal/mol). To evaluate dynamic stability, selected complexes were subjected to molecular dynamics simulations. The results showed that 2-Acrylamido-2-methyl-1-propanesulfonic acid exhibited the lowest average energy (-76.301 kcal/mol), followed by p-vinylbenzoic acid (-70.03 kcal/mol) and 4-vinylbenzeneboronic acid (-69.70 kcal/mol). Metadynamics simulations further confirmed this trend, with total energy (Etot) values of -76.23 kcal/mol, -69.96 kcal/mol, and -69.64 kcal/mol for the same monomers, respectively. The consistency between molecular dynamics and metadynamics analyses indicates that 2-Acrylamido-2-methyl-1-propanesulfonic acid forms the most energetically stable complex with esculetin under simulated conditions. This study provides a computational basis for selecting functional monomers for esculetin recognition systems and supports further experimental validation.